Corporate Risk Management Strategies Using Big Data and Predictive Analytics - Syahputra, Hendri; Effendy, Faried; Al-Amin, Al-Amin (International Journal of Social Science, Education, Communication and Economics, 2025)
Digital transformation has brought significant changes in the corporate risk management landscape. The application of Big Data and predictive analytics provides new opportunities for companies to identify, monitor and control risks more effectively and efficiently. This research aims to examine the implementation strategy of Big Data and predictive analytics in corporate risk management through the literature review method. The results show that the integration of these technologies can improve early detection of risks, accelerate data-based decision-making, and automate the risk mitigation process. However, successful implementation is strongly influenced by the readiness of technological infrastructure, human resource competence, data governance, and management commitment. With the right strategy, companies can build an adaptive, responsive and highly competitive risk management system in the digital era.